Seed extract of Moringa oleifera used for reducing the numbers of thermotolerant coliforms on seabob shrimp, Xiphopenaeus kroyeri - Vieira, Regine Helena Silva dos Fernandes; Vieira, Cláudia Brandão; de Sousa, Oscarina Viana; Vieira, Gustavo Hitzschky Fernandes; Filho, Antonio Adauto Fonteles (Arquivos de Ciências do Mar, 2009)
The present paper has addressed the reductive action of the saline extract of “moringa” (Moringa oleifera) on thermotolerant coliforms (TC) found in seabob shrimp (Xiphopenaeus kroyeri) sold on the Mucuripe fi sh market, Fortaleza, Ceará State, under the immersion time periods of 5, 10, 15 and 20 min. Each sample was broken down into three groups, namely SCS – shrimp control sample, MTS – moringa-treated shrimp, and STS – saline-treated shrimp. Sensorial analyses were carried out with SCS e STS in order to ascertain the extract infl uence on shrimp-food fl avor. The Most Probable Number (MPN) of TC per gram of shrimps had values varying from < 3.0 to 1,000 encompassing the fourteen experiments, out of which twelve (85.71%) showed a decrease in TC after immersion in “moringa” extract. From a total of 61 strains isolated from shrimp samples before and after treatment with “moringa” extract, were identifi ed 27 ones of E. coli I, 21 of Klebsiella spp, nine of Enterobacter spp and four of Citrobacter spp. The 5-min immersion time period was chosen for a second batch of experiments to be conducted, and according to their results, the saline “moringa” extract was found to have a reducing effect on the biomass of thermotolerant coliforms in the shrimp sold at the Mucuripe fi sh market, Fortaleza, Ceará State.